Digital Disruption and Social Cohesion: Challenges and Opportunities for Communities (Open Society Conference, 2025)
Digital disruption has fundamentally changed social interactions, creating challenges and opportunities for social cohesion in communities. This research examines the complex interactions between technology and society, emphasizing that successful communities are those that are able to balance the use of technology for connectivity with authentic face to face interactions. Using normative legal research methods and a case study approach, this research analyzes legal literature such as Law Number 11 of 2008 on Electronic Information and Transactions, as well as other relevant regulations. The results show the importance of digital literacy and social media ethics programs to equip individuals with the ability to think critically and interact responsibly in online spaces. Communities also need to consciously integrate online and offline interactions to ensure technology is a complement, not a substitute, for meaningful personal relationships, in order to create resilient, inclusive and adaptive communities in the future.